Cultura e mundo moderno em Georg Simmel : uma filosofia da vida do espírito - Schardosim, Ivan Krás Borges (2021)
This dissertation aims at discussing the problem of culture under the thought of Georg Simmel, trying to show, through classical works of his, such as The Philosophy of Money (1900) and the essays on the cities, the vital relation between the tragedy of culture and the modern style of life. For Simmel, the movement of the spirit is inductor of its own ruin, in a way that most things that it creates and invents ends up returning as a torrent of things and exaggerations, frivolities and perditions; in short, as an “avalanche”, which means, for Simmel, the actuation of objective culture upon subjective culture. Several are the consequences of this process. For one side, what historically conformed the idea of individual was lost of sight. For another, technique gained strength – a “means” that became an end. Modernities, in this regard, outstrip ever quicker what endures, what gives stability. What used to unite us now separates us. To present this rich interpretation of the times, we make use of two strategies: 1) to unfold what the Berliner author meant by culture and tragedy of culture; and 2) through an investigation of his analyses on the cities and the urban life, to dissertate on how the style of life, for Simmel, reveals the true essence of modernity. Lastly, through a dialogue with some of his interpreters, we take on a discussion about Simmel‟s historical-philosophical contribution.